2021
DOI: 10.3390/s21175776
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning-Based Wi-Fi Indoor Positioning System Using Continuous CSI of Trajectories

Abstract: In a Wi-Fi indoor positioning system (IPS), the performance of the IPS depends on the channel state information (CSI), which is often limited due to the multipath fading effect, especially in indoor environments involving multiple non-line-of-sight propagation paths. In this paper, we propose a novel IPS utilizing trajectory CSI observed from predetermined trajectories instead of the CSI collected at each stationary location; thus, the proposed method enables all the CSI along each route to be continuously enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In [26], the authors propose a deep residual sharing learning based IPS which uses the 2DCNN to exploit both frequency and time features in bimodal CSI data. In [25], Zhang et al propose utilizing the trajectory CSI to enhance the robustness of the instability of RF signals in the indoor environment. They employ an 1DCNN to extract the spatial information from the trajectory CSI.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [26], the authors propose a deep residual sharing learning based IPS which uses the 2DCNN to exploit both frequency and time features in bimodal CSI data. In [25], Zhang et al propose utilizing the trajectory CSI to enhance the robustness of the instability of RF signals in the indoor environment. They employ an 1DCNN to extract the spatial information from the trajectory CSI.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, deep learning (DL) based algorithms are gaining a keen interest in the application of IPS. Some related works [22], [23], [24], [25], [26] have shown that the DL algorithms such as dense neural network (DNN), convolutional neural network (CNN), long short-term memory (LSTM), etc. can help the IPS better capture the correlation between the fingerprint and corresponding position, which consequently enhances the accuracy compared to the conventional methods [27], [28].…”
Section: Introductionmentioning
confidence: 99%
“…LSTM-based tracking methods have also been proposed for indoor environments recently. For instance, in [20], [21], continuous CSI measurements of trajectories were first represented as deep features via a CNN network and then the features were fed into an LSTM network for tracking purposes. However, these learning-based tracking methods are designed under a specific environment and their generality is poor.…”
Section: B Csi-based Trackingmentioning
confidence: 99%
“…• LSTM-F: we compare with the LSTM-based tracking method proposed in [20], [21]. Following [20], we first train an AAResCNN using all the training samples.…”
Section: B Tracking Across Environmentsmentioning
confidence: 99%
See 1 more Smart Citation